Using Virtual Laboratory Online System: "Wiley-Anatomy Drill and Practice" as an learning media for health workers - Joel Rey U. Acob; Heru Santoso Wahito Nugroho; Sanglar Polnok (Aloha International Journal of Health Advancement (AIJHA), 2018)
-